Síntese hidrotérmica de uma Ni-MOF a partir do carbonato de níquel e do ácido glutâmico - Silva, Luana Thayline Casagrande (2024)
MOFs (Metal–Organic Frameworks) are crystalline and porous structures belonging to the class of coordination polymers, which are calling the attention of researchers for studies of new materials and synthetic routes, especially when the synthesis processes are simple and low cost. These compounds have several applications and among some of them are the storage of gases, the use as catalysts in heterogeneous syntheses and in pharmacology, through the controlled release of drugs. In this direction, this work aims to synthesize MOFs of the type BioMOFs (Metal–Organic Frameworks for Biological and Medical Applications) or MbioFs (Metal Biomolecules Frameworks) using glutamic acid and nickel carbonate as precursors. Initial results indicated the formation of a complex, [Ni(Hglutamate)2] which, when placed in a Teflon-coated stainless steel autoclave at 100 ºC for 24 hours, resulted in the compound [Ni(glutamate)(H2O)·H2O]n, with a yield of 43%. This compound, which appears as a crystalline solid with an intense green color, was characterized by vibrational spectroscopy in the Infrared region by Fourier transform (FTIR), X-ray powder diffraction (PXRD) and in single crystal (DRX) and analysis thermogravimetry (TGA). Preliminary analysis indicate the formation of a MOF-like structure belonging to the orthorhombic crystalline system and space group P212121, analogous to the structures of the compounds [Co(glutamate)(H2O)·H2O]n [Cu(glutamate)(H2O)·H2O]n and [Zn(glutamate)(H2O)·H2O]n described in the literature. It also has the molecular formula C5H9NO5Ni·H2O, molar mass of 239.8379 g mol-1, parameters a, b and c, with values respectively of 7.0577(2) (Å), 10.2307(3) (Å) and 11.5350(4) (Å) and volume of 837.219 (Å3). The toxicity and antimicrobial activity of the complex and Ni-MOF were tested, where the two compounds do not present toxicity against Drosophilas melanogaster flies at a concentration of 5000 ppm, nor inhibitory activity against gram positive and gram negative bacteria, but with activity inhibitory at 62.5 μg/mL in 24 h and at 125 μg/mL in 48 h against the yeast Candida albicans.